Comparison of Management for Central Venous Stenosis With or Without Previous Catheter Placement - Ma, Wei; Zhao, Zhengde; Fu, Qining; Hu, Liangzhu; Zhao, Xia; Wang, Chao; Liu, Yangdong (Frontiers in Neurology, 2021)
Objective: To compare central venous stenosis/occlusion with or without previous jugular catheter placement history. Methods: Data of patients with central vein stenosis/occlusion receiving endovascular intervention in our hospital from January 2015 to December 2018 were collected and analyzed. Results: Twenty-nine patients with previous jugular catheter placement history (CVC group) and 33 patients (excluded two with technical failure) without such history (non-CVC group) are included in this study. Previous jugular catheter placement history raised the risk of postintervention recurrence 1.02 times (CVC group vs. non-CVC group, HR = 2.02 95%CI: 0.91–4.48). The primary patency rate at 6, 12, 18, and 24 months was 76.9, 54.2, 45.5, and 25.0% separately in the CVC group and 80.6, 70.0, 67.9, and 44.4% separately in the non-CVC group. The assisted primary patency rate at 6, 12, 18, and 24 months was 92.3, 91.7, 86.4, and 68.8% separately in the CVC group and 93.5, 90.0, 82.1, and 61.1% separately in the non-CVC group. Patients in the CVC group received a higher frequency of reintervention (0.7 times/year/patient vs. 0.3 times/year/patient). There was no significant difference in the assisted primary patency rate between the two groups. Different primary interventions (angioplasty alone, bare metal stent, stent graft) did not affect primary patency and assisted primary patency, but percutaneous transluminal stenting (PTS) with a bare metal stent had a significant lower primary patency rate between 3 and 24 months compared with PTS with a stent graft (p = 0.011). Conclusion: Central venous stenosis/occlusion with a previous jugular catheter placement history develops symptoms earlier and had a worse prognosis after endovascular intervention. More efforts are needed to carry out end-stage kidney disease life plan to reduce the harm of evitable catheter placement.